1962
DOI: 10.1084/jem.115.4.867
|View full text |Cite
|
Sign up to set email alerts
|

A Transient Stage of Suspected Delayed Sensitivity During the Early Induction Phase of Immediate Corneal Sensitivity

Abstract: 1. If quantities of bovine serum albumin or bovine gamma globulin in the range of 2 to 4 mg are inoculated intracorneally into rabbits, a biphasic reaction occurs in the cornea. 2. The primary reaction, which becomes manifest approximately 3 days after inoculation and lasts several days, is characterized by a diffuse clouding of the cornea. During this period, no antibody can be demonstrated either by serological or histological techniques. The animals react with a delayed type of skin reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1963
1963
1978
1978

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In a previous study, the present authors demonstrated that if a sufficient quantity of antigen is introduced intracorneally in rabbits, one obtains a biphasic reaction in that cornea (6). The initial response is characterized by a sudden diffuse corneal clouding and a dilatation of the limbal vessels 3 to 5 days after the introduction of the antigen.…”
Section: (From the Wilmer Ophthalmological Institute Of The Johns Hopmentioning
confidence: 50%
See 1 more Smart Citation
“…In a previous study, the present authors demonstrated that if a sufficient quantity of antigen is introduced intracorneally in rabbits, one obtains a biphasic reaction in that cornea (6). The initial response is characterized by a sudden diffuse corneal clouding and a dilatation of the limbal vessels 3 to 5 days after the introduction of the antigen.…”
Section: (From the Wilmer Ophthalmological Institute Of The Johns Hopmentioning
confidence: 50%
“…The most recent observations on the induction of delayed hypersensitivity by means of immune precipitates serve to further emphasize the importance of the intradermal route. It was therefore with much excitement that the present authors added their observation of an experimentally induced, biphasic corneal reaction, representing a transient stage of delayed hypersensitivity prior to the appearance of the antibody mediated "Wessely Phenomenon," to the literature (6).…”
Section: Discussionmentioning
confidence: 98%
“…Morawiecki (1956) demonstrated that the cornea could behave much like an agar substrate for migration of immune reactants in producing precipitin arcs as in gel diffusion. Parks et al (1962) revealed a delayed hypersensitivity response in the cornea if it was overloaded with antigen in attempts to produce the Wessely phenomenon. The cornea was used for many years as the critical in-vivo test for delayed hypersensitivity to a given antigen (Salvin and Gregg, 1961). )…”
mentioning
confidence: 99%